Diffusion-Weighted Imaging of Orbital Masses: Multi-Institutional Data Support a 2-ADC Threshold Model to Categorize Lesions as Benign, Malignant, or Indeterminate - Sepahdari, A.R.; Politi, L.S.; Aakalu, V.K.; Kim, H.J.; Razek, A.A.K. Abdel (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: DWI has been increasingly used to characterize orbital masses and provides quantitative information in the form of the ADC, but studies of DWI of orbital masses have shown a range of reported sensitivities, specificities, and optimal threshold ADC values for distinguishing benign from malignant lesions. Our goal was to determine the optimal use of DWI for imaging orbital masses through aggregation of data from multiple centers. MATERIALS AND METHODS: Source data from 3 previous studies of orbital mass DWI were aggregated, and additional published data points were gathered. Receiver operating characteristic analysis was performed to determine the sensitivity, specificity, and optimal ADC thresholds for distinguishing benign from malignant masses. RESULTS: There was no single ADC threshold that characterized orbital masses as benign or malignant with high sensitivity and specificity. An ADC of less than 0.93 × 10−3 mm2/s was more than 90% specific for malignancy, and an ADC of less than 1.35 × 10−3 mm2/s was more than 90% sensitive for malignancy. With these 2 thresholds, 33% of this cohort could be characterized as “likely malignant,” 29% as “likely benign,” and 38% as “indeterminate.” CONCLUSIONS: No single ADC threshold is highly sensitive and specific for characterizing orbital masses as benign or malignant. If we used 2 thresholds to divide these lesions into 3 categories, however, a majority of orbital masses can be characterized with >90% confidence. ROCreceiver operating characteristic analysis